1991
DOI: 10.1116/1.585595
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low temperature SiO2 and Si3N4 films deposited by plasma enhanced evaporation

Abstract: SiO2 and Si3N4 films have been deposited at low temperatures by a new plasma enhanced evaporation process. The films are stoichiometric and have hydrogen contents below 1 at. %. For the electrical characterization metal–insulator–semiconductor diodes were fabricated and investigated before and after annealing in H2/N2 atmosphere at 430 °C. Ellipsometric and capacitance–voltage measurements yield the dielectric constants which agree well with the theoretical values. From conductance–voltage characteristics the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Most studies concluded that the conduction mechanisms in thin SiN x films are bulk-controlled [17,23,24], while some have found indications for space-charge-limited conduction (SCLC) [25], or field emission [26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Most studies concluded that the conduction mechanisms in thin SiN x films are bulk-controlled [17,23,24], while some have found indications for space-charge-limited conduction (SCLC) [25], or field emission [26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is about the same as generally found in production grade Si 3 N 4 /Si interfaces formed by the thermal LPCVD deposition of silicon nitride at temperatures in the range of 750 to 850°C. 38 Figure 7 displays the high frequency C -V characteristics of Al/SiN x :H/InP samples with PMA carried out at different temperatures for 45 min in forming gas. There are significant differences between the C -V characteristics of these structures and those shown in Fig.…”
Section: B C -V Characteristicsmentioning
confidence: 99%
“…Although comparison to other film resistivities is clouded by the variations in measurement and film preparation techniques, the low bias resistivities measured in this work compare with that of thermally grown SiO 2 , which also has reported values of 10 15 -10 17 Xcm. [55][56][57] The leakage current at larger biases, however, is significantly impacted by the efficacy of hydrogen's ability to break weak bonds, as is shown in the current density versus electric field (J-E) curves in Figures 8(a) and 8(b) for silaneand TMS-based films, respectively. The quasi-saturation in current density observed in lower deposition temperatures, resulting in the ledge-shape of the curve, is a result of charge trapping.…”
Section: E Electrical Propertiesmentioning
confidence: 99%